Differentiated instruction science learning for intellectually disabilities pupils at an inclusive primary school: a case study - Yunaini, Norma; Mustadi, Ali; Mumpuniarti, .; Ishartiwi, .; Hidayat, Riyan (Ekip Buro Makineleri A., 2024)
Differentiated instruction (DI) is an approach to learning that allows teachers to meet the unique needs of pupils in the classroom. This study aimed to explore the extent to which DI is implemented in learning to improve the science process skills (SPS) of Intellectually Disabilities (ID) pupils in inclusive primary school education. This research was of the qualitative study type with case study design in 5 inclusive primary schools in Indonesia. The subjects of the study were five teachers who had experience teaching in inclusive primary schools. The sampling method used was purposive sampling, while the data collection the technique used is an in-depth interview. For data analysis techniques, content analysis and descriptive qualitative analysis were used. The results showed that teachers still face challenges in implementing DI for ID pupils in science subjects in inclusive primary schools, despite efforts to understand and implement DI, teacher readiness is still limited, especially in terms of: 1) planning the implementation of learning according to the needs of ID pupils; 2) plan teaching materials that are in accordance with the abilities of ID pupils; 3) lack of DI-related teacher training and coaching in inclusive primary schools. The implication of this study is the need to increase teacher readiness in implementing DI effectively for pupils with special needs, especially in science in inclusive primary schools.